Franklin D.D. Shane and Rachel A. Shane land grant - Shane, Franklin D. D.; Shane, Rachel A.
Grant, signed by James A. Garfield, issued to Franklin D.D. and Rachel A. Shane for land in Clatsop County, Or.
Negative photocopy.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Garfield, James A. -- 1831-1881.; Land grants -- Oregon -- Clatsop County